Recycled waste materials in concrete construction : emerging research and opportunities - Mirza, Jahangir, 1944-; Hussin, Mohd Warid, 1951-; Ismail, Mohamed A., 1968- (Engineering Science Reference, 2019)
"This book discusses the different type of industrial, agricultural and/or natural wastes and how some have been already utilized in the concrete industry while many others demonstrate promise for future use"-- Provided by publisher
Keywords: Waste products as building materials.; Concrete construction -- Environmental aspects.; elektronické knihy; electronic books